2022
DOI: 10.3390/w14071171
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrate-Based Heavy Metal Ion Removal from Industrial Wastewater: A Review

Abstract: Innovating methods for treating industrial wastewater containing heavy metals frequently incorporate toxicity-reduction technologies to keep up with regulatory requirements. This article reviews the latest advances, benefits, opportunities and drawbacks of several heavy metal removal treatment systems for industrial wastewater in detail. The conventional physicochemical techniques used in heavy metal removal processes with their advantages and limitations are evaluated. A particular focus is given to innovativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 168 publications
0
6
0
Order By: Relevance
“…This better fit to the pseudo-second order model suggests that this process is not solely dependent on physical forces (such as diffusion) but involves a significant contribution from chemical in-teractions between Sb and MIPs 46 . The results reveal that MIP-206-NH 2 demonstrated significantly higher capacity compared to other materials documented in the literature 47 49 . Moreover, MIP-206-NH 2 reached its maximum capacity in a notably shorter time compared to previously reported materials, underscoring the superior performance of MIP-206-NH 2 in Sb separation.…”
Section: Resultsmentioning
confidence: 69%
“…This better fit to the pseudo-second order model suggests that this process is not solely dependent on physical forces (such as diffusion) but involves a significant contribution from chemical in-teractions between Sb and MIPs 46 . The results reveal that MIP-206-NH 2 demonstrated significantly higher capacity compared to other materials documented in the literature 47 49 . Moreover, MIP-206-NH 2 reached its maximum capacity in a notably shorter time compared to previously reported materials, underscoring the superior performance of MIP-206-NH 2 in Sb separation.…”
Section: Resultsmentioning
confidence: 69%
“…Seaweed is an important component of the marine ecosystem and comprises macroalgae (seaweed) and microalgae, which share common characteristics and photosynthetic capacity, but are different in size and morphology (NALLAKUKKALA et al, 2022). Seaweed grows in a wide variety of marine environments throughout the year and can achieve high growth without relying on arable land, chemicals, or fertilizers (MALAKA et al, 2020).…”
Section: Marine Biopolymer-based Bioplasticmentioning
confidence: 99%
“…Heavy metals are highly toxic and stable in aquatic environments and do not degrade. They can build up in significant amounts in the human body once they reach the food chain and cause serious health issues when metals are consumed beyond the allowed concentration limit [ 13 , 14 , 15 ]. On the other hand, a recent report demonstrated that heavy metals contribute to the heterogeneity of water environments via metal–algae interaction.…”
Section: Introductionmentioning
confidence: 99%